Injuries and associated factors in practitioners of combat sports – Karate - Hadad, Sâmia Maria; Val, Helosine Martins Moreira Lima; Neto, Edjard Pinto da Silveira; Rios, Mateus Fernandes; Oliveira, Marcele Martins; Campos, Jorge William de Sá; Lopes, Jefferson Campos; Mariano, Eder Rodrigo; Pires, Flávio de Oliveira; Filho, Almir Vieira Dibai; Souza, Sérgio Augusto Rosa de (Seven Editora, 2024)
Introduction: Karate is a martial art of Japanese origin that means "path of empty hands". As a Combat Sports Modality (MEC), it made its debut as an Olympic modality at the Tokyo Games in Japan in 2021. In its fighting essence, it mostly uses attack and defense techniques with hands, feet, elbows and knees. This fact, combined with the continuous contact and intensity of the training, among other aspects, favor the occurrence of injuries in its practice. Objective: This study aimed to verify the association between sociodemographic factors and the practice of the modality with the occurrence of injuries in karate practitioners in the State of Maranhão, Brazil. Methods: This was a quantitative study with a descriptive cross-sectional character. Data collection was carried out through the Questionnaire Injuries in Combat Sports Modalities (QLGS1), administered in person in the practice/teaching spaces of the modality and remotely through a link made available on Google Forms. Data were analyzed using descriptive statistics (mean, standard deviation and frequency distribution). The chi-square test was used to verify the association between the variables. Values of p≤0.05 were considered significant. This study was approved by the Research Ethics Committee of the Federal University of Maranhão (CEP/UFMA) No. 4,711,629. Results: A total of 68 Karate practitioners from the state of Maranhão participated in this investigation, with a mean age of 31.53 years (SD=12.513), of both sexes (75.0% male), age group 30 years or older (47.1%), level of education – higher and graduate (75.0%) and monthly family income of up to three minimum wages (44.1%). Regarding the modality and its practice, 14 years was the average training time (SD=11.919), participate in competitions (29.4%), do not practice another MEC (80.9%), practice another sport/physical activity to improve performance in Karate (67.6%), have been injured (63.2%), Knees (46.51%) and Wrists/Hands (46.51%) were the regions of the body most affected by injuries and, Concussion (60.4%) and Dislocation (39.5%) were the types of injuries most mentioned by the participants. Participating or not in competitions, frequency of training/week and practicing another sport/physical activity to improve performance in Karate were the variables that showed statistically significant differences with the occurrence or not of injuries. Conclusion: In this investigation, ECM – Karate – presented a high rate of injuries, with the Knees and Wrists/Hands being the most affected regions and Concussion and Dislocation being the most reported types. The occurrence of injuries was associated with some variables related to the practice of the modality, such as participation or not in competitions and weekly frequency of training. The relevance of interventions related to injury prevention for a healthier practice in the modality and a better quality of life of its practitioners is highlighted. DOI:https://doi.org/10.56238/sevened2024.012-049